TÜRKİYE'DE KORONAVİRÜSÜN İLK HAFTASINDAKİ TOPLUMSAL ALGILANIŞI ÜZERİNE BETİMSEL BİR ANALİZ. - YILDIZ, Hülya; KUTLU, İhsan (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2022)
In this study, the opinions of the participants about the coronavirus and their level of application of the described measures were examined. Using the descriptive research model, one of the quantitative research methods, a cross-sectional survey was carried out with easy sampling. The online questionnaire form was delivered to the participants and the data obtained were analyzed using various computer programs. The obtained findings were visualized with tables and graphics and a descriptive analysis was made. In the analyzes, in addition to percentage and frequency information, multiple correspondence analysis was also used. The data were collected between 15-18 March 2020. A total of 313 people participated in the study, but the participants under the age of 18 were not included in the analysis, and the data of 303 people were processed. While people generally expressed positive opinions about the attitudes of themselves and their close circle about the coronavirus process, they expressed negative opinions about the society. On the other hand, it was found that the participants were acting cautiously regarding protection from coronavirus. As a result of the study, it was understood that people closely followed the epidemic process and turned to various measures to prevent the disease. In this context, it is possible to state that people have started to behave cautiously about the disease, without official restrictions yet.